Knowledge based firms from Central and East European countries: A comparative overview of case studies - Richard Woodward; Deniz Eylem Yörük; Slavo Radosevic (Center for Social and Economic Research (CASE), 2011)
This paper focuses on knowledge-based entrepreneurship, or new firm creation in industries which are considered to be science-based or to use research and development intensively, in the East Central European (ECE) context. On the basis of case studies of thirteen knowledge-based firms in six ECE countries, we suggest that KBE firms in these countries may differ in some important ways from the conventional picture of new technology based firms. In general, we see the ECE knowledge-intensive firm as a knowledge-localiser or customiser, adapting global knowledge to local needs on the domestic market, rather than a knowledge-creator generating new solutions for global markets. The entrepreneurs who start and run these businesses are skilled at spotting trends early and bringing them to their countries. Based in countries that generally have poor reputations as sources of innovative, high-technology products, but having established strong brands for themselves in their home markets, they are struggling with the challenge of entering export markets with products and services that can achieve global, or at least regional, recognition. The studies of the companies discussed here suggest that ECE firms are still in the early stages of this strategic shift.
Keywords: L26; O31; O52; P27; 330; Knowledge-based economy; Entrepreneurship; Transition; Post-communist; SMEs; Case studies; Croatia; Czech Republic; Hungary; Lithuania; Poland; Romania; Wissen; Wissensgesellschaft; Industrieforschung; Innovation; Entrepreneurship-Ansatz; Unternehmensgründung; KMU; EU-Mitgliedschaft; Kroatien